Evaluation of Compliance for Treatment of Sudden Hearing Loss: A CHEER Network Study. (July 2016) - Witsell, David L.; Khoury, Tawfiq; Schulz, Kristine A.; Stachler, Robert; Tucci, Debara L.; Wojdyla, Daniel
Objective: The objective of this study is to describe the presentation and management of sudden sensorineural hearing loss for patients seen in academic and community-based practices within the context of the American Academy of Otolaryngology—Head and Neck Surgery Foundation's "Clinical Practice Guideline: Sudden Hearing Loss." The intention is to use these findings to guide implementation strategies and quality improvement initiatives and as pilot data for the development of clinical research initiatives. Study Design: A cross-sectional study of patients with sudden hearing loss. Setting: Patients were recruited from practices within the Creating Healthcare Excellence through Education and Research (CHEER) network. The CHEER network is an National Institutes of Health–funded network of 30 otolaryngology sites across the country, half of which are community based and half of which are academic practices. Subjects and Methods: A total of 173 patients were recruited. Data were gathered via custom questionnaires collected by study site coordinators and entered into a secure online platform. Descriptive analyses and correlation statistics were run with SAS 9.3.1. Results: Of the 13 guideline statements in the American Academy of Otolaryngology—Head and Neck Surgery Foundation's clinical practice guideline on sudden hearing loss, 11 statements were evaluable through this study. Compliance for otolaryngologists was >95% for key action statements (KASs) 1, 3, and 6; 90% to 95% for KASs 5 and 10; and <90% for KASs 7 and 13. Compliance was <45% for nonotolaryngologists for KASs 3 and 5-7. Conclusions: There is opportunity for nonotolaryngologists to improve for statements 3 and 5-7. Otolaryngologists are compliant with many of the KASs overall, but there is significant room for improvement.